An Introduction to the Science of Cosmology - Raine, Derek ((Series in Astronomy and Astrophysics))
Contenido: 1) Reconstruyendo el tiempo; 2) Expansión; 3) Materia; 4) Radiación; 5) Relatividad; 6) Modelos; 7) Big Bang caliente; 8) Inflación; 9) Estructura; 10) Epílogo.